Qualitative Dissertation Methodology : A Guide for Research Design and Methods - Durdella, Nathan (SAGE, 2019)
"It's no secret doctoral students struggle to write their dissertations, particularly the methodology chapter. Qualitative Dissertation Methodology: A Guide for Research Design and Methods, by Nathan Durdella, helps students construct a qualitative methodological framework for their research, write it up, and continue onto the rest of the dissertation with confidence. With a warm and supportive tone, the author walks students through the process of constructing this framework from the very start, from to choosing chairs and developing qualitative support networks, outlining the qualitative chapter and delving into the writing, and setting students up for further work on their dissertations" --